Soil nutrient content dominates short-term vegetation changes in alpine tundra of Changbai Mountains - Xing, Shanfeng; Wang, Wen J.; Wang, Lei; Du, Haibo; Wu, Zhengfang; Zong, Shengwei; Cong, Yu; Ba, Shengjie (Frontiers in Microbiology, 2024)
Alpine tundra, covering 3% of the Earth’s land surface, harbors approximately 4% of higher plant species. Changes in this vegetation significantly impact biodiversity and ecosystem services. Recent studies have primarily focused on large-scale and long-term vegetation changes in polar and high-latitude regions. However, the study of short-term vegetation changes and their primary drivers has received insufficient attention in alpine tundra. This study aimed to investigate vegetation changes and their dominant drivers in the alpine tundra of Changbai Mountains-located at the southern edge of the alpine tundra distribution in Eastern Eurasia-over a short period by re-surveying permanent plots in 2019 and comparing them with data from 2014. The results showed that significant changes were observed in alpine tundra vegetation during the study period. The importance values of typical alpine tundra plants such as Rhododendron chrysanthum, Vaccinium uliginosum, and Dryas octopetala decreased noticeably, while those of herbaceous species such as Deyeuxia angustifolia and Sanguisorba sitchensis increased significantly. Species richness, diversity, and evenness at different altitudinal gradients showed varying degrees of increase. A distinct expansion trend of herbaceous species was observed in the alpine tundra, contributing to a shift in plant community composition toward herbaceous dominance. This shift might result in the meadowization of the dwarf shrub tundra. Our findings further revealed that soil nutrients rather than climate factors, dominated the changes of plant communities over a short period. These findings provide scientific references for the conservation and management of biodiversity, as well as for projecting future vegetation dynamics in alpine tundra.